2019
DOI: 10.3389/fimmu.2018.03039
|View full text |Cite
|
Sign up to set email alerts
|

Relative Frequencies of Alloantigen-Specific Helper CD4 T Cells and B Cells Determine Mode of Antibody-Mediated Allograft Rejection

Abstract: Humoral alloimmunity is now recognized as a major determinant of transplant outcome. MHC glycoprotein is considered a typical T-dependent antigen, but the nature of the T cell alloresponse that underpins alloantibody generation remains poorly understood. Here, we examine how the relative frequencies of alloantigen-specific B cells and helper CD4 T cells influence the humoral alloimmune response and how this relates to antibody-mediated rejection (AMR). An MHC-mismatched murine model of cardiac AMR was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 61 publications
3
27
0
Order By: Relevance
“…The contribution of humoral alloimmunity to transplant failure is increasingly recognized (13). In addition to acute antibody mediated rejection (AMR) that typically occurs early after transplantation [considered in the companion paper (4)], donor specific alloantibody (DSA) responses are associated with chronic graft dysfunction, progressive allograft vasculopathy and early graft failure (5). Chronic AMR is less well-defined, and not recognized as a distinct clinical entity for some organs (6).…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of humoral alloimmunity to transplant failure is increasingly recognized (13). In addition to acute antibody mediated rejection (AMR) that typically occurs early after transplantation [considered in the companion paper (4)], donor specific alloantibody (DSA) responses are associated with chronic graft dysfunction, progressive allograft vasculopathy and early graft failure (5). Chronic AMR is less well-defined, and not recognized as a distinct clinical entity for some organs (6).…”
Section: Introductionmentioning
confidence: 99%
“…and alloantibody29,30 reactions in the progression of allograft vasculopathy, and our ongoingF I G U R E 3 Donor T-reg depletion results in exacerbated autoantibody production and accelerated graft loss. Heart allografts from unmodified (WT) or T-reg-depleted bm12 donor mice were transplanted into WT C57BL/6 mice and effector autoantibody responses (A) and allograft rejection (B) were assessed.…”
mentioning
confidence: 98%
“…This process appears to be multifactorial, as illustrated by a recent study using a murine model of ABMR. This study showed that a relative higher number of antigen‐specific helper T cells compared to B cells is evoking a strong extrafollicular response while a relative predominance of B cells promotes germinal centre reactions (Alsughayyir et al., 2018). Germinal centre‐experienced B cells can leave germinal centres as isotype‐switched memory B cells or plasma cells producing high‐affinity HLA antibodies.…”
Section: The Humoral Immune Response In Kidney Transplantationmentioning
confidence: 99%